2012
DOI: 10.1186/1472-6831-12-15
|View full text |Cite
|
Sign up to set email alerts
|

Parental reports of the oral health-related quality of life of children with cerebral palsy

Abstract: BackgroundThe severity of physical and mental impairments and oral problems, as well as socioeconomic factors, may have an impact on quality of life of children with cerebral palsy (CP). The aim of this research was to assess the impact of impairments and oral health conditions, adjusted by socioeconomic factors, on the Oral Health-Related Quality of Life (OHRQoL) of children with CP using their parents as proxies.MethodsSixty children, between 6-14 years of age were selected. Their parents answered a children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
89
4
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(113 citation statements)
references
References 26 publications
8
89
4
11
Order By: Relevance
“…Conversely, house property [21] and house ownership [14] were not found to be significant, but one study on 12-year-old school children of Juiz de For, Brazil, reported that children whose parents owned a house had better OHRQoL than those who do not own a house [4] only in bivariate analysis. A study on Chilean adolescents found number of cars owned and monthly paternal income to be significantly associated with OHRQoL, while house ownership was insignificant [37].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, house property [21] and house ownership [14] were not found to be significant, but one study on 12-year-old school children of Juiz de For, Brazil, reported that children whose parents owned a house had better OHRQoL than those who do not own a house [4] only in bivariate analysis. A study on Chilean adolescents found number of cars owned and monthly paternal income to be significantly associated with OHRQoL, while house ownership was insignificant [37].…”
Section: Resultsmentioning
confidence: 99%
“…This study carried out the description and verification of factors associated with the impact on HRQoL and OHRQoL of children and adolescents with CP. Despite using a nonprobabilistic sample, it is important to note that the number of subjects examined is much higher than that of other Brazilian and international studies that evaluated OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the OHRQoL scores according to the oral complications, lower values were found in individuals with dental caries or periodontal diseases. Many authors report that dental caries had an impact on the OHRQoL of children with CP . The occurrence of this impact can be explained by the signs and symptoms of dental caries that can hamper the activities of children with CP, such as eating, drinking, sleeping, and playing and worry parents, because the lack of communication makes it difficult to express discomfort, and often causes uncertainty and frustration in parents …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tooth decay and other oral defects negatively impact a child's quality of life as assessed by children and parents (Barbosa and Gavião, 2008;Nurelhuda et al, 2010;de Castro et al, 2011;Aguilar-Díaz et al, 2011;Biazevic et al, 2008;Abanto et al, 2012;Krisdapong et al, 2012;Bönecker et al, 2012;Locker, 2007). Quality of life impacts have also been found for dental fluorosis, but there is a marked difference in physical appearance and quality of life assessments for children with moderate/severe dental fluorosis compared with those having none/ questionable or very mild/mild forms.…”
mentioning
confidence: 91%